Presence of a monoclinic (Cc) phase in the (1-x)BiFeO3-xCaTiO3 solid solution nanoparticles: A Rietveld study - Kumar V.; Singh A.K.; Singh S. (My University, 2025)
We present here the results of structural investigations on magnetoelectric multiferroic (1 - x)BiFeO3-xCaTiO3 (BF-xCT) solid solution nanoparticles, synthesized by the sol-gel method, using Rietveld analysis on powder x-ray diffraction data in the compositional range of 0 ≤ x ≤ 0.60. The stability of various crystallographic phases in BF-xCT solid solution nanoparticles at room temperature is determined accurately. The structure of BF-xCT solid solution nanoparticles is monoclinic (Cc) for 0.10 ≤ x ≤ 0.22 and orthorhombic (Pbnm) for x ≥ 0.28, whereas the two phases coexist in the morphotropic phase boundary region of 0.23 ≤ x ≤ 0.27 as confirmed by Rietveld analysis. We have established the phase diagram at room temperature for BF-xCT solid solution nanoparticles as a function of composition. Transmission electron microscopy confirmed the morphology, microstructure, and the crystallinity of the nanoparticles, and the average particle size is found to be in the range of 30-50 nm. © 2017 Author(s).